Driving Parameters for Multi‐MeV Electrons Flux Variations in Outer Radiation Belt. Issue 11 (27th October 2021) - Behailu, G.; Nigussie, M.; Reeves, G. D.; Wing, S.
Abstract: The Earth's outer radiation belt is highly dynamic and the variations of multi‐MeV electrons flux in the region depend on solar wind and interplanetary magnetic field ( I M F ) parameters. This study attempts to characterize the causality and timing of the solar wind and IMF parameter activities on the outer radiation belt environment based on three tools: time shifted cross correlation, mutual information, and transfer entropy statistical analysis. The Van Allen Probes mission measurements of multi‐MeV (3.4–6.3 MeV) electrons flux data in the period from January 01, 2017 to December 31, 2018 have been used. The results indicate that the information transfer from solar wind and IMF parameters into multi‐MeV electrons flux is dependent on the kind of driving parameter, range of L‐shell, and energy of electrons. The result identifies the rank of driving parameters based on their maximum values in the correlation and information transfer analysis. Thus, solar wind velocity is the dominant driving parameter for the variation of multi‐MeV electrons flux in the outer radiation belt. Given three ranges of L‐shell ( ∼ 4, ∼ 4.5 and ∼ 5 ), with decreasing L‐shell values the maximum information transfer from driving parameters into electron flux decreases and the lag time increases. Such dependency analysis can help to select the model parameters that influence the variation of multi‐MeV electrons flux and improve the existed models of the dynamical system. Key Points: The information transfer from solar wind and interplanetary magnetic field parameters into multi‐MeV electrons flux have been analyzed using dependency analysis tools From driving parameters, V s w is the dominant parameter in causing multi‐MeV electrons flux variation Information transfer lag time is dependent on ranges of L‐shell and energy of the electron in the outer radiation belt